Socioeconomic status, Marriage Patterns, and Fertility Choices in Jordan - Hailat, Mahmoud (Jordan Journal of Economic Sciences, 2015)
This paper examines the effect of socioeconomic conditions, mainly individual education, parents’ education, wealth status, dowry, and place of residence on marriage decision and fertility choices in Jordan. For this purpose, cross sectional micro-data of Jordan Labor market Survey (JLMS) 2010 is used. Logit models and standard linear regression models are employed in the analysis. Main findings can be summarized as follows. Individual’s own education is more critical for marriage and fertility than parents’ education. Patterns of marriage reflect preference for partners with some education over illiterates, while involvement in university and higher education postpones marriage by 2.5 to 3 years. People tend to marry younger and have more children two decades ago than they do recently. Moreover, individuals in the second, third, and fourth strips of wealth are more likely to marry earlier than the poorest and the richest, whereas fertility declines as wealth increases. No evidence on regional differences regarding marriage and fertility. However, age at marriage and fertility may differ across governorates rather than regions. Individuals in larger households are more likely to marry younger and produce more children. Finally, further investigation is needed to explore the role of parents’ education and cost of marriage.